Visualising trade-related virtual urban land transfers in China - Jieyang Xiong; Liwei Wang; Tao Song; Haimeng Liu (Regional Studies, Regional Science)
As a type of environmental footprint, the concept of virtual land captures the indirect land use embedded in our consumption and trade activities. Utilising the environmentally-extended multi-regional input–output model (EEMRIO) and Kaleidoscope diagram, we visualise for the first time the interprovincial flow of virtual urban land in China. It unveils the intricate urban network connections and the telecoupled interactions between human activities and land use amidst China's rapid urbanisation phase. The results indicate that the eastern region of China emerges as the primary net beneficiary of virtual urban land, whereas the western region stands as the principal net contributor. The local urban land in 65% of the provinces suffices for their own consumption demands. However, provinces like Zhejiang, Henan, and Jiangsu rely heavily on inter-provincial urban land to fulfil their consumption requirements. Inter-regional trade plays a pivotal role in facilitating the flow of land resources, significantly easing the strain between human demands and land availability in the developed coastal provinces of eastern China. Yet, it imposes additional ecological pressure on the more ecologically vulnerable areas in the west. The insights from this research are poised to offer valuable guidance for the Chinese government in harmonising urban development strategies, industrial distribution and the allocation of construction land on a national scale.